Comparative study of English and Uzbek adverbial clauses (Texas Journal of Philology, Culture and History, 2022)
This article covers a comparative view of adverbial clauses in English and Uzbek languages, and presents the similarities and differences between them. Problematic areas of using adverbial clauses are provided and suggestions are given for Uzbek learners while learning English